The impact of pandemic A(H1N1)pdm09 influenza and vaccine-associated adverse events on parental attitudes and influenza vaccine uptake in young children - Blyth, C.; Richmond, P.; Jacoby, P.; Thornton, P.; Regan, Annette; Robins, C.; Kelly, H.; Smith, D.; Effler, P. (Elsevier, 2014)
Introduction: Parental attitudes towards vaccination significantly influence vaccine uptake. The A(H1N1)pdm09 influenza pandemic was followed in 2010 by an unprecedented increase in febrile reactions in children receiving trivalent inactivated influenza vaccine manufactured by bioCSL. Uptake of TIV in children < 5 years in Western Australia (WA) decreased in 2010 and has remained low. The impact of pandemic A(H1N1)pdm09 and adverse-events on parental attitudes towards vaccination is uncertain. Materials and Methods: A parental attitudes survey towards influenza illness and vaccination was conducted as part of the West Australian Influenza Vaccine Effectiveness study. Vaccination status was assessed by parental interview and confirmed by the national register and/or vaccine providers. Parental attitudes from vaccinated and unvaccinated children and attitudes in 2008-2009 and 2010-2012 were compared. Principal Component Analysis was conducted to determine core attitudes that influenced vaccine uptake. Results: Vaccination history and parental attitude surveys were available from 2576 children. Parents of fully vaccinated children less frequently stated that influenza was a mild disease, more frequently stated that influenza vaccine was safe and were less frequently worried about vaccine side effects. Uptake of influenza vaccine decreased significantly from 2010 onwards. From 2010, parents were less concerned about severe influenza, but more concerned about vaccine side effects and safety. Despite this significant shift in attitudes towards influenza vaccine, parental acceptance of vaccines on the national immunisation program did not change. Principal Component Analysis revealed that attitudes around vaccine safety and efficacy were the most important attitudes impacting on vaccine uptake. Conclusions: Parental attitudes to influenza vaccine changed from 2010. Confidence in the WA preschool influenza vaccination program remains low yet appeared unchanged for other vaccines. Restoring public confidence in childhood influenza vaccination is needed before uptake can be improved.